Live Shopping TikTok dalam Perspektif Ekonomi Syariah serta Keberlanjutan Pasar - Anggita Putri Kinanti; Karimah, Annisa Dzakiah; Karmila, Karmila; Fahra, Cindy Aulia (Universitas Islam Raden Rahmat, 2024)
The development of technology has changed the way people transact. Live shopping features allow sellers and buyers to interact directly. TikTok launched a live shopping feature to facilitate transactions. This feature has a positive impact for both sellers and buyers. For sellers, this feature reaches more buyers. For buyers, live shopping makes it easier to get the desired item. However, this feature has also sparked debate. It is considered to be incompatible with Sharia principles and can damage the market. The study uses qualitative methods with secondary data from news articles and publications, as well as primary data from observations and interviews. The study's findings point out that TikTok's live shopping content does not yet completely adhere to the principles of Sharia. Some of the contents that are not in line include content that promotes haram products, deceptive content, and predatory pricing, it also adversely affects the market as it can lead to unhealthy competition.